The collector [compact disc, unabridged] - Roberts, Nora (Brilliance Audio, 2013)
"As a professional house-sitter and freelance writer, nothing ties Lila Emerson down--not her work, not a home, and definitely not a relationship. She spends her life moving from one job to the next, sometimes crashing at a friend's Manhattan apartment. And though she can appreciate her clients' extraordinary homes, their expensive collections, and their adorable pets, Lila has never longed for possessions of her own. Everything she has, including her heart, is portable. But when she witnesses a possible murder-suicide from her current apartment-sitting job, life as Lila knows it takes a dramatic turn. Artist Ashton Archer knows his charming, clever, and impulsive brother couldn't have killed his girlfriend--or taken his own life. His hope of unraveling what happened lies with Lila, the only eyewitness. And even buried in grief, Ash longs to paint the woman whose deep, dark eyes seem to hold endless reserves of strength and a fiery passion. Chalking up their intense attraction to the heat of the moment, Lila agrees to help Ash in trying to find out who murdered his brother and why. From the penthouses of Manhattan to grand Italian villas, their investigation draws them into a rarefied circle where priceless antiques are bought, sold, gambled away, and stolen, where what you possess is who you are, and where what you desire becomes a deadly obsession" --